El papel del periodismo gastronómico como construcción de una identidad culinaria en Ecuador. - Vinueza Chiriboga, María Valentina (2025)
Contemporary gastronomic journalism in Ecuador has undergone a transformation in recent decades where superficial coverage of narratives that articulate cultural and social identity elements is present in the media, mainly television programs such as MasterChef Celebrity Ecuador. The research is based on an intersection of studies based on communication and the construction of national identity, where the results of the study show that gastronomic journalism is an active agent and the construction of identity narratives, mainly. The research is a mixture of qualitative methodology in which it was possible to carry out an analysis of the content published on the main social network, in this case Instagram, of MasterChef Celebrity Ecuador, and with the interviews of experts in the field of communication and former participants of this same television program, with which we were able to collect information for the triangulation of data. The quantitative methodology was used to carry out the analysis of the contents, mainly where the interaction, the number of comments and even the times in which users interact or share the content that is published is measured. The research concludes that gastronomic journalism in Ecuador is a cultural mediator that preserves and transforms the national culinary identity, where the theoretical implications suggest a contextualization of identity as a dynamic process for the development of cultural policies, where the media emerge as a pillar in the democratization of gastronomic knowledge.